Cost and affordability of healthy, equitable and more sustainable diets in the Torres Strait Islands - Amanda J. Lee; Dori Patay; Susannah Summons; Meron Lewis; Lisa‐Maree Herron; Francis Nona; Condy Canuto; Megan Ferguson; Aletia Twist (Elsevier, 2022)
Abstract Objectives: To assess the cost, cost differential and affordability of current and recommended (healthy, equitable, culturally acceptable and more sustainable) diets in the Torres Strait Islands and compare with other Queensland locations. Methods: The Aboriginal and Torres Strait Islander Healthy Diets ASAP (Australian Standardised Affordability and Pricing) methods protocol was applied in five randomly selected communities in the Torres Strait Islands. Results: The current diet was 32% more expensive than that recommended; 'discretionary' foods comprised 64% of the current diet cost. Families could save at least A$281.38 a fortnight by switching to recommended diets. However, these cost 35‐40% more than elsewhere in Queensland. Recommended diets would cost 35% of median and 48% of welfare household income in the Torres Straits. Conclusions: While less expensive than the current diet, recommended diets are unaffordable for most households. Consequently, many Torres Strait Islander families are at high risk of food insecurity and diet‐related disease. Implications for public health: Urgent policy action is required to further lower the relative price of recommended diets, and also increase household incomes and welfare supplements to equitably improve food security and diet‐related health, and contribute to environmental sustainability in the Torres Strait Islands.